If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a(4a + -9) = 0 Reorder the terms: 2a(-9 + 4a) = 0 (-9 * 2a + 4a * 2a) = 0 (-18a + 8a2) = 0 Solving -18a + 8a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '2a'. 2a(-9 + 4a) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(-9 + 4a)' equal to zero and attempt to solve: Simplifying -9 + 4a = 0 Solving -9 + 4a = 0 Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4a = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4a = 0 + 9 4a = 0 + 9 Combine like terms: 0 + 9 = 9 4a = 9 Divide each side by '4'. a = 2.25 Simplifying a = 2.25Solution
a = {0, 2.25}
| x^2+8=3x | | (w^2-5*w-6)+(3w^2-4*w+2)= | | X(2x-3)=43 | | -6x^2+13x=-5 | | 171-3x=42x+21 | | 174-2x=25x+21 | | 12-9x=25-16x | | (n+w)*2=48 | | 10x-4=2x+6 | | 12-9x=93-30x | | 3+3r-2=6r+5-2r | | (15+2x)(11+2x)=525 | | 2x+14=36-8x | | 98-4x=3x+21 | | 5+r-6-r=13 | | 6x-(-8)=50 | | 6(2.25k-5.5)=10.5-k | | 6x=x-3(21) | | -4.6-1m+2m=3.4 | | n^2-2n+72= | | -4.6-m+2m=3.4 | | n^2-2n+72=0 | | 47-5x=22x+17 | | 6-7x=29-14x | | -5(3b+3)+(16b-8)=0 | | 3x+17=13x-3 | | -126+7x=8x+24 | | 10x-17=93 | | 42=42y | | 2w+2n=48 | | -126-7x=29-14x | | 2z+4=5z+8 |